2016
DOI: 10.1177/1687814016667418
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element evaluations of debonding in composite sandwich structure with core thickness variations

Abstract: An important failure mode in sandwich structures is the debonding between the core and facesheet, which can destroy the load capacity of the structure. This work addressed the critical interfacial modes and studied the effects of thickness variation of the core material. The single cantilever beam geometry is utilized for conducting experiments after optimizing the thicknesses of the core and facesheet by minimizing the difference in the bending stiffness matrix between the upper facesheet and the lower facesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…4 shows, in a log-log scale, upper and lower bound values of the crack length correction and asymptotic limiting solutions on varying the ratio E f /E c . The crack length correction which would be obtained with the common assumption of an equivalent thickness equal to h c and a foundation modulus k = bE c /h c (e.g., [9][10][11]29,32]) is given by Δ = h f E f h c /3E c h f 4 and shown in the diagram with thin dotted lines for varying h c /h f in the range E f /E c > 1. Comparing these solutions to the bounds shows that the assumption h = h c overestimates the crack length correction for all materials examined, with 1 ≤ E f /E c ≤ 10000, when h c ≥ 10h f ; for these geometrical ratios the upper bounds values should be used at all times.…”
Section: Foundation Modulus In Sandwichesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 shows, in a log-log scale, upper and lower bound values of the crack length correction and asymptotic limiting solutions on varying the ratio E f /E c . The crack length correction which would be obtained with the common assumption of an equivalent thickness equal to h c and a foundation modulus k = bE c /h c (e.g., [9][10][11]29,32]) is given by Δ = h f E f h c /3E c h f 4 and shown in the diagram with thin dotted lines for varying h c /h f in the range E f /E c > 1. Comparing these solutions to the bounds shows that the assumption h = h c overestimates the crack length correction for all materials examined, with 1 ≤ E f /E c ≤ 10000, when h c ≥ 10h f ; for these geometrical ratios the upper bounds values should be used at all times.…”
Section: Foundation Modulus In Sandwichesmentioning
confidence: 99%
“…Different foundation moduli have been used in the analysis of DCB and SCB sandwich fracture specimens, e.g., [9][10][11]29,32], [19,20], and k SCB,DCB = bE cm /h c [21,23], based mainly on simple extensions of Kanninen's modulus or by fitting the energy release rate of the approximate models to casespecific finite element results; E c , h c , h f , b are core transverse modulus, core, and face-sheet thicknesses and specimen width; E cm is a parameter depending on the elastic constants of the core, which has been derived through an elasticity-based approach in Refs. [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the initiation and propagation values of delamination toughness remained constant for specimens with a specific range of the initial crack length to the specimen thickness ratio. Saeid and Donaldson 4 considered the critical interfacial modes and studied the effect of different core thicknesses on the fracture of sandwich structures. Ghadirdokht and Heidari-Rarani 5 investigated the effect of unidirectional composite laminates curvature on the behavior of delamination R-curve experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…Gibson's [4] research was about how to minimize the weight of a sandwich panel for given structural requirements by adjusting the density and thickness of faces or the core. Recently, Saeid and Donaldson [1] studied on the effects of thickness variation of the core material on the load capacity of the structure through experiments. Their experimental results showed that the critical energy release rate could be influenced by core thickness variations.…”
mentioning
confidence: 99%
“…Their experimental results showed that the critical energy release rate could be influenced by core thickness variations. Other than the thickness studies, the geometry effects on the structure are also extensively studied [1] [3] [4] [13] [14] [15]. For example, Konsta [3] focused on how the geometry of the core can affect the failure mode by comparing foam and honeycomb core design.…”
mentioning
confidence: 99%